2013
DOI: 10.1155/2013/857586
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Microstructure Characterization of Metakaolin‐Based Geopolymer Containing Oil Palm Ash

Abstract: This study reports on the microstructure, compressive strength, and drying shrinkage of metakaolin (MK) based geopolymers produced by partially replacing MK by oil palm ash (OPA). The OPA was used as raw material producing different molar ratios of SiO2/Al2O3 and CaO/SiO2. The geopolymer samples were cured at 80°C for 1, 2, or 4 hours and kept at ambient temperature until testing. The compressive strength was measured after 2, 6, and 24 hours and 7 and 28 days. The testing results revealed that the geopolymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…Kupaei et al identified an increase in the compressive strength of foamed cements as coal fly ash was partially replaced by palm oil fuel ash, which was attributed to the higher water demand of the coal ash and thus the need to add more water to achieve satisfactory workability, and Liu et al also developed low‐density structural insulating materials from this combination of precursors. Hawa et al added palm oil fuel ash to alkali‐activated metakaolin, which was able to decrease the tendency towards drying shrinkage of these alkali‐activated cements.…”
Section: Agro‐industrial Wastesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kupaei et al identified an increase in the compressive strength of foamed cements as coal fly ash was partially replaced by palm oil fuel ash, which was attributed to the higher water demand of the coal ash and thus the need to add more water to achieve satisfactory workability, and Liu et al also developed low‐density structural insulating materials from this combination of precursors. Hawa et al added palm oil fuel ash to alkali‐activated metakaolin, which was able to decrease the tendency towards drying shrinkage of these alkali‐activated cements.…”
Section: Agro‐industrial Wastesmentioning
confidence: 99%
“…Fernandez‐Jiménez and Palomo suggested that a suitable coal FA must have loss on ignition values lower than 5% . However, there exist studies related to the production of alkali‐activated materials using different industrial wastes or by‐products derived from thermal processes with higher contents of organic matter, including coal fly ash, coal bottom ash, municipal solid waste ashes, palm oil fuel ash, and sugar cane bagasse ash . Considering that the high content of un‐reacted material reduces the effectiveness and reactivity of these wastes as precursors, blending with another more‐reactive aluminosilicate may be required.…”
Section: Summary and General Considerationsmentioning
confidence: 99%
“…During the last two decades, there have been a number of researchers who focused their efforts to utilize geopolymer concrete due to the wide range of potential applications [8,9,15]. The effect of single and binary combination of binders among MK, GGBS, and POFA has been reported by previous researchers [28][29][30]. Islam et al [13] reported the highest compressive strength of about 66 MPa by using 70% GGBS with 30% POFA.…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al [22] reported that foamed concrete incorporating POFA enhanced compressive, flexure, splitting tensile strength, and ductility. Hawa et al [29] evaluated the performance and microstructure characterization of metakaolin based geopolymer concrete containing POFA.…”
Section: Introductionmentioning
confidence: 99%